A method for preparing amorphous metal oxide positive electrode material and its application

Through a new preparation method of amorphous metal oxide positive electrode material, the problem of insufficient structural stability and electrochemical performance of the positive electrode material of sodium ion battery is solved by using organic sodium salt and inorganic salt templates, and efficient and stable battery performance and the effect of reducing production costs is achieved.

CN119038635BActive Publication Date: 2025-04-08NINGBO VEKEN BATTERY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411547505.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-04-08
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The positive electrode materials of sodium ion batteries have shortcomings in terms of structural stability and electrochemical performance, especially because the large ion radius of sodium ions leads to slow migration speed, which leads to cation ordering and charge ordering, resulting in capacity attenuation and reduced stability.

Method used

Using a preparation method of an amorphous metal oxide positive electrode material, an amorphous NaxNiyMn1-yOz metal oxide is formed by stirring and dissolving the organic manganese salt, an organic nickel salt and an organic sodium salt in a solvent, adding an inorganic salt solution and then drying and heating. This method provides sodium ions through organic sodium salts and regulates the microstructure of the material through inorganic salt templates to improve the specific surface area and pore distribution of the material.

Benefits of technology

It significantly improves the electrochemical performance and structural stability of the cathode material of sodium ion battery, enhances the discharge capacity, rate performance and cycle stability, reduces production costs and energy consumption, and simplifies the process flow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119038635B_ABST
    Figure CN119038635B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of positive electrode materials for sodium ion batteries, and relates to a preparation method and application of an amorphous metal oxide positive electrode material. The preparation method comprises the following steps: (1) stirring and dissolving an organic manganese salt and an organic nickel salt in a solvent, and then adding an organic sodium salt and continuing to stir to obtain a solution A; (2) dissolving an inorganic salt in water and stirring to obtain a solution B, and adding the solution B to the solution A and continuing to stir to obtain a mixed solution C; (3) drying the mixed solution C to obtain a mixed powder, heating and keeping the mixed powder warm, washing the product after cooling, and freeze-drying to obtain the target product, an amorphous metal oxide positive electrode material. The present invention innovatively uses a unique combination of an organic sodium salt, an organic manganese salt and an organic nickel salt to successfully synthesize an amorphous manganese-based oxide rich in sodium ions, and realizes effective doping of nickel elements, thereby increasing the voltage platform and specific capacity, and improving the performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials and relates to a preparation method of an amorphous metal oxide positive electrode material and application thereof. Background Art

[0002] The cathode material of sodium-ion batteries is crucial to their capacity and power. Therefore, the development of cathode materials with high performance, low cost and structural stability has become a core challenge to improve the performance of sodium-ion batteries. At present, the main cathode materials used include layered metal oxides, polyanion compounds and Prussian blue analogs. It is particularly noteworthy that layered transition metal oxides are favored due to their high energy density, high voltage platform, excellent rate performance, simple preparation process and low cost. Among these layered oxides, manganese-based Na x MnO2 has attracted extensive attention due to the cost-effectiveness of manganese and its ease of chemical modification.

[0003] However, Na x MnO2 materials also face some challenges due to the sodium ion (Na + ) has a large ionic radius and its migration speed in the material is slow, which may lead to cation ordering and charge ordering phenomena; in addition, the material also has irreversible phase change and transition metal ion dissolution problems, which will cause structural damage and ultimately lead to capacity decay and reduced stability. Although doping with nickel (Ni) can improve the voltage platform and specific capacity, it still fails to completely solve the problem of structural stability.

[0004] In contrast, amorphous metal oxides can accelerate the Na + Due to its isotropic properties, there are no grain boundaries and dislocations, so it can effectively relieve internal stress during ion insertion and deinsertion, thereby enhancing structural stability. Therefore, using amorphous metal oxides as positive electrode materials for sodium ion batteries is expected to improve the energy density and cycle stability of batteries.

[0005] In summary, constructing amorphous metal oxides as the positive electrode material of sodium-ion batteries can improve the energy density and cycle stability of the battery. However, the synthesis of amorphous materials cannot achieve the same controllability as crystals. This is because the synthesis and control of crystals rely on the inherent directionality of the lattice, which is undoubtedly not applicable to isotropic amorphous materials.

[0006] Therefore, the development of a new and stable amorphous metal oxide and its preparation method has become a key challenge that needs to be urgently solved in this field. To meet this challenge, researchers need to explore innovative synthesis techniques to ensure that the resulting materials not only have excellent electrochemical properties, but also maintain long-term structural stability. The ideal preparation method should be able to achieve effective control of the composition and microstructure while ensuring the amorphous properties of the material, thereby overcoming the limitations of the lack of precise regulation in the synthesis of traditional amorphous materials. By overcoming this problem, it is expected to promote the advancement of sodium-ion battery technology and further expand its application potential in large-scale energy storage systems. Summary of the invention

[0007] The present invention aims at the problems existing in the positive electrode materials of sodium ion batteries in the prior art and provides a method for preparing an amorphous metal oxide positive electrode material and an application thereof.

[0008] One object of the present invention is achieved by the following technical solutions:

[0009] A method for preparing an amorphous metal oxide positive electrode material, the preparation method comprising the following steps:

[0010] (1) stirring and dissolving an organic manganese salt and an organic nickel salt in a solvent, then adding an organic sodium salt and continuing to stir to obtain a solution A;

[0011] (2) dissolving an inorganic salt in water and stirring to obtain solution B, adding solution B to solution A and continuing to stir to obtain a mixed solution C;

[0012] (3) The mixed solution C is dried to obtain a mixed powder, the mixed powder is heated and kept warm, the product is washed after cooling, and the target product, an amorphous metal oxide positive electrode material, is obtained by freeze-drying.

[0013] The organic manganese salt includes one or more of manganese acetylacetonate, manganese acetate and manganese oxalate.

[0014] The organic nickel salt includes one or more of nickel acetylacetonate, nickel acetate, and nickel oxalate.

[0015] The organic sodium salt includes one or more of sodium carboxylate, sodium oxalate and sodium squarate.

[0016] The inorganic salt includes one or more of potassium bromide, sodium nitrate, sodium chloride and sodium carbonate.

[0017] The present invention utilizes organic sodium salt as a sodium source, which not only provides sodium ions during the synthesis process, but also may participate in the formation of specific crystal or amorphous structures; at the same time, organic manganese salt and organic nickel salt are combined to provide manganese and nickel metal elements; the inorganic salt template plays a role in regulating the microstructure of the material, so that the finally prepared material has a higher specific surface area and a better pore distribution, thereby improving the electrochemical performance of the material.

[0018] Preferably, in step (1), the mass ratio of the organic manganese salt, the organic nickel salt and the organic sodium salt is (1-10):(1-7):(1-10).

[0019] Preferably, in step (1), the solvent is a polar solvent, including one or more of dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), sulfolane, and acetonitrile. More preferably, dimethylformamide is used.

[0020] Preferably, in step (1), the organic manganese salt and the organic nickel salt are stirred in a solvent for 0.5 to 1 hour, and after the organic sodium salt is added, stirring is continued for 0.5 to 1 hour, and the stirring temperature is 30 to 60°C.

[0021] Preferably, in step (2), the concentration of the inorganic salt in solution B is 0.1-0.2 mol / L.

[0022] Preferably, in step (2), solution B is added to solution A and stirring is continued for 3 to 4 hours to obtain a mixed solution C.

[0023] Preferably, in step (2), the mass ratio of the inorganic salt to the organic sodium salt in the mixed solution C is (1-3):(1-5).

[0024] Preferably, in step (3), the mixed solution C is dried at 60-90° C. for 0.5-10 h to obtain a mixed powder.

[0025] Preferably, in step (3), the mixed powder is heated to 260-300° C. in an air atmosphere at a heating rate of 5-10° C. / min and kept warm for 2-4 h.

[0026] Preferably, in step (3), the product is washed at least twice with a mixture of water and ethanol in a volume ratio of (1-2):(1-2).

[0027] The second object of the present invention is achieved by the following technical solutions:

[0028] An amorphous metal oxide positive electrode material is prepared by the above preparation method.

[0029] Preferably, the amorphous metal oxide positive electrode material has the general formula of Na x Ni y Mn 1-y O z , where 0.2≤x≤0.9, 0<y<1, 1≤z≤2.

[0030] The third object of the present invention is achieved by the following technical solutions:

[0031] A sodium ion battery positive electrode plate comprises the above-mentioned amorphous metal oxide positive electrode material.

[0032] Preferably, the positive electrode plate comprises an amorphous metal oxide positive electrode material, a conductive agent and a binder.

[0033] Preferably, the method for preparing the positive electrode sheet of a sodium ion battery comprises the following steps: ball-milling and mixing an amorphous metal oxide positive electrode material, a conductive agent, and a binder, adding a solvent to form a positive electrode slurry, and then coating, vacuum drying, and rolling to obtain a positive electrode sheet of a sodium ion battery.

[0034] Preferably, the mass ratio of the amorphous metal oxide positive electrode material, the conductive agent, the binder and the solvent is (90-100): (0.1-5.0): (0.1-5.0): (20-50).

[0035] Preferably, the conductive agent includes one or more of conductive carbon black Super P, Super S, graphene, carbon nanotubes, and carbon fibers.

[0036] Preferably, the binder includes one or more of PVDF, polyvinylidene fluoride, polyvinyl alcohol, and polytetrafluoroethylene.

[0037] Preferably, the solvent includes one or more of N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), ethanol, isopropanol, and acetone.

[0038] The fourth object of the present invention is achieved by the following technical solutions:

[0039] A sodium ion battery comprises the above-mentioned sodium ion battery positive electrode plate.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. The present invention provides an amorphous metal oxide positive electrode material. By innovatively combining an organic sodium salt with an organic manganese salt and an organic nickel salt, an amorphous manganese-based oxide rich in sodium ions is successfully synthesized, and effective doping of nickel elements is achieved to improve the voltage platform and specific capacity.

[0042] 2. The present invention provides an amorphous metal oxide positive electrode material, amorphous Na x Ni y Mn 1-y O z Metal oxides are relatively x MnO2 metal oxide effectively improves its gram capacity and material stability. The technical solution of the present invention not only enhances the performance of the positive electrode material itself, but also significantly improves the overall performance of the battery after applying it to battery manufacturing, significantly enhancing the discharge capacity of the battery and improving the rate performance; the material also enhances the working performance of the battery in high and low temperature environments, which is crucial for broadening the application range of sodium ion batteries; the material also improves the battery cycle stability, which means that the battery can still maintain a high capacity retention rate after multiple charge and discharge cycles, thereby extending the battery life.

[0043] 3. The present invention provides a method for preparing an amorphous metal oxide positive electrode material. Compared with the traditional solid phase method and liquid phase method, the method of the present invention has significant advantages. The traditional solid phase method includes ball milling and mixing the metal oxide with a sodium source and then calcining it at high temperature; the liquid phase method is to generate a precursor by coprecipitation reaction between a metal salt and an alkaline solution, and then mix it with a sodium source and calcine it at high temperature. Although these two methods can prepare the required positive electrode materials, the process flow is often complicated and the cost is high. In contrast, the new process flow provided by the present invention is simpler to operate, greatly simplifies the production process, and reduces energy consumption and production costs. Due to its simple process and low cost, this method can not only greatly reduce the use cost of the positive electrode material itself, but also reduce the cost of manufacturing the raw materials of the battery cell, thereby providing a more economical and feasible solution for large-scale production and application. This is not only conducive to reducing the price of end products, but also promotes the commercialization of sodium ion battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a TEM image of the amorphous metal oxide positive electrode material of Example 1 of the present invention.

[0045] Figure 2 This is a SEM image of the amorphous metal oxide positive electrode material of Example 1 of the present invention.

[0046] Figure 3 This is a high-resolution image of the amorphous metal oxide positive electrode material of Example 1 of the present invention.

[0047] Figure 4 This is the XRD spectrum of the amorphous metal oxide positive electrode material of Example 1 of the present invention.

[0048] Figure 5This is a comparison chart of the discharge specific capacity of sodium ion batteries prepared with the amorphous metal oxide positive electrode material of Example 1 of the present invention and the crystalline metal oxide positive electrode material of Comparative Example 1 at different rates.

[0049] Figure 6 This is a comparison chart of the cycle performance of sodium ion batteries prepared using the amorphous metal oxide positive electrode material of Example 1 of the present invention and the crystalline metal oxide positive electrode material of Comparative Example 1. DETAILED DESCRIPTION

[0050] The technical solution of the present invention is further described below in conjunction with specific embodiments and drawings. It should be understood that the specific embodiments described herein are only used to illustrate the present invention and are not used to limit the scope of the present invention. And the drawings used herein are only for better illustrating the disclosed content of the present invention and do not have a limiting effect on the scope of protection. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0051] Example 1

[0052] The preparation method of the amorphous metal oxide positive electrode material in this embodiment includes the following steps:

[0053] (1) Dissolve 0.27 g of manganese acetylacetonate and 0.15 g of nickel acetylacetonate in 100 mL of dimethylformamide, stir at 45 °C for 0.5 h, add 0.32 g of sodium carboxylate and continue stirring for 0.5 h to obtain solution A;

[0054] (2) Dissolve 0.223 g potassium bromide in 100 mL deionized water and stir to obtain solution B. Slowly add 50 mL of solution B into solution A at 35°C and continue stirring for 3 h to obtain a mixed solution C.

[0055] (3) The mixed solution C was placed in a watch glass and dried at 85°C for 0.5 h to obtain a mixed powder. The mixed powder was placed in a porcelain boat and heated to 285°C in an air atmosphere using a muffle furnace at a heating rate of 5°C / min and kept warm for 2 h. The mixture was then naturally cooled to room temperature. The product was washed several times with a deionized water-ethanol mixed solution and freeze-dried to obtain the target product, amorphous Na 0.66 Ni 0.6 Mn 0.4 O 1.73 Metal oxide positive electrode materials.

[0056] Example 2

[0057] The preparation method of the amorphous metal oxide positive electrode material in this embodiment includes the following steps:

[0058] (1) Dissolve 0.25 g of manganese acetylacetonate and 0.18 g of nickel acetylacetonate in 100 mL of dimethylformamide, stir at 45 °C for 0.5 h, add 0.35 g of sodium carboxylate and continue stirring for 0.5 h to obtain solution A;

[0059] (2) Dissolve 0.228 g potassium bromide in 100 mL deionized water and stir to obtain solution B. Slowly add 60 mL of solution B into solution A at 35°C and continue stirring for 4 h to obtain a mixed solution C.

[0060] (3) The mixed solution C was placed in a watch glass and dried at 85°C for 0.5 h to obtain a mixed powder. The mixed powder was placed in a porcelain boat and heated to 285°C in an air atmosphere using a muffle furnace at a heating rate of 5°C / min and kept warm for 4 h. The mixture was then naturally cooled to room temperature. The product was washed several times with a deionized water-ethanol mixed solution and freeze-dried to obtain the target product, amorphous Na 0.68 Ni 0.6 Mn 0.4 O 1.76 Metal oxide positive electrode materials.

[0061] The morphology and phase characterization of the amorphous metal oxide positive electrode material of Example 1 were observed using an electron microscope. The specific results are shown in Figures 1 to 4 .

[0062] Figure 1 TEM image of the amorphous metal oxide positive electrode material of Example 1 of the present invention; Figure 2 This is a SEM image of the amorphous metal oxide positive electrode material of Example 1 of the present invention; Figure 3 This is a high-resolution image of the amorphous metal oxide positive electrode material of Example 1 of the present invention; Figure 4 This is the XRD spectrum of the amorphous metal oxide positive electrode material of Example 1 of the present invention.

[0063] from Figures 1 to 4 It can be seen that the technical solution of the present invention successfully prepared amorphous Na x NiMnO2 metal oxide positive electrode material, the present invention innovatively uses sodium carboxylate and organic metal salt to synthesize sodium-rich manganese-based oxide, and at the same time realizes nickel doping. The present invention uses salt template and organic metal salt for full adsorption during mixing, making the reaction more complete and ensuring the amorphous Na x The element ratio and morphology of NiMnO2 metal oxide positive electrode material are more uniform.

[0064] Comparative Example 1

[0065] The preparation method of the crystalline metal oxide positive electrode material of this comparative example comprises the following steps:

[0066] Amorphous Na 0.66 Ni 0.6 Mn 0.4 O 1.73 The metal oxide cathode material was then annealed at 350 °C for 2 h in an Ar / H2 (90% / 10%) atmosphere. The resulting product was washed several times with a deionized water-ethanol mixture and dried to obtain crystalline Na 0.66 Ni 0.6 Mn 0.4 O 1.73 Positive electrode material.

[0067] The positive electrode materials of Example 1 and Comparative Example 1 are used to prepare a sodium ion battery, comprising the following steps: weighing the positive electrode materials, conductive carbon black SP, PVDF binder and NMP solvent prepared in Example 1 and Comparative Example 1 at a mass ratio of 100:5:5:50; ball-milling the positive electrode material, conductive carbon black SP and PVDF binder, adding NMP solvent and stirring evenly, maintaining high-speed stirring for 5 hours, with a revolution speed of 400 m / s and a dispersion speed of 30 m / s to form a positive electrode slurry; then coating it on aluminum foil, vacuum drying at 100° C. and rolling it to obtain a positive electrode sheet; then assembling the positive electrode sheet, the counter electrode sheet (metallic sodium), an electrolyte (solute is NaPF6, the concentration is 1 mol / L, and the solvent is EC:DEC=1:1) and a glass fiber separator to obtain a sodium ion battery, and performing relevant battery performance tests, and the specific test method is as follows.

[0068] 1. Discharge capacity test at different rates

[0069] First, the battery was placed in an environment of 25±2℃ for 8h, then charged to 4.8V at a constant current of 0.5C, followed by standing for 5min, then charged at a constant voltage of 4.8V to a current of 0.05C, stood for 5min, and then discharged at a constant current of 0.1C / 0.2C / 0.5C / 1.0C to a voltage of 2.8V. The resulting capacity was recorded as the 0.1C / 0.2C / 0.5C / 1.0C discharge capacity.

[0070] 2. Cycle performance test.

[0071] First, place the battery in a 25±2℃ environment for 8h, then charge it to 4.8V at a constant current of 0.5C, then let it stand for 5min, then charge it at a constant voltage of 4.8V to a current of 0.05C, let it stand for 5min, then discharge it to 2.8V at a constant current of 0.5C, repeat the above cycle for 150 times, and finally stop the operation, record the discharge capacity from the 1st to the 150th cycle, and calculate the capacity retention rate as follows:

[0072] The nth cycle capacity retention rate = the nth cycle discharge capacity / the 1st cycle discharge capacity (1≤n≤150).

[0073] For detailed test results, see Figures 5 and 6 .

[0074] Figure 5 The discharge specific capacity comparison diagram of the sodium ion battery prepared by the amorphous metal oxide positive electrode material of Example 1 of the present invention and the crystalline metal oxide positive electrode material of Comparative Example 1 at different rates. Among them, the discharge rate of the amorphous metal oxide positive electrode material at 0.1C is 140mAh / g, and the discharge rate of the crystalline metal oxide positive electrode material is 130mAh / g; the discharge rate of the amorphous metal oxide positive electrode material at 0.2C is 135mAh / g, and the discharge rate of the crystalline metal oxide positive electrode material is 125mAh / g; the discharge rate of the amorphous metal oxide positive electrode material at 0.5C is 128mAh / g, and the discharge rate of the crystalline metal oxide positive electrode material is 120mAh / g; the discharge rate of the amorphous metal oxide positive electrode material at 1.0C is 122mAh / g, and the discharge rate of the crystalline metal oxide positive electrode material is 118mAh / g.

[0075] Figure 6 This is a comparison chart of the cycle performance of sodium ion batteries prepared using the amorphous metal oxide positive electrode material of Example 1 of the present invention and the crystalline metal oxide positive electrode material of Comparative Example 1.

[0076] from Figures 5 and 6 It can be seen that compared with the crystalline material, the amorphous metal oxide positive electrode material synthesized by the technical solution of the present invention effectively improves the manganese-based Na x The specific capacity and stability of MnO2 metal oxide can effectively improve the discharge capacity, rate performance and cycle stability of the battery cell after it is made into a battery cell.

[0077] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0078] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0079] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A method for preparing an amorphous metal oxide positive electrode material, characterized in that: The preparation method comprises the following steps: (1) Stirring the organic manganese salt and the organic nickel salt in a solvent for 0.5 to 1 h, then adding the organic sodium salt and continuing stirring for 0.5 to 1 h at a stirring temperature of 30 to 60 ° C to obtain solution A; (2) dissolving an inorganic salt in water and stirring to obtain solution B, adding solution B containing the inorganic salt to solution A containing an organic sodium salt and continuing to stir for 3 to 4 hours to obtain a mixed solution C; (3) Drying the mixed solution C at 60-90°C for 0.5-10 h to obtain a mixed powder; heating the mixed powder to 260-300°C in an air atmosphere at a heating rate of 5-10°C / min and keeping the temperature for 2-4 h; washing the product after cooling, and freeze-drying the product to obtain the target product, an amorphous metal oxide positive electrode material; The organic manganese salt includes one or more of manganese acetylacetonate, manganese acetate, and manganese oxalate; The organic nickel salt includes one or more of nickel acetylacetonate, nickel acetate, and nickel oxalate; The organic sodium salt includes one or both of sodium oxalate and sodium squarate; The inorganic salt includes one or more of potassium bromide, sodium nitrate, sodium chloride, and sodium carbonate; In the step (2), the concentration of the inorganic salt in solution B is 0.1-0.2 mol / L.

2. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of the organic manganese salt, the organic nickel salt and the organic sodium salt is (1-10):(1-7):(1-10).

3. The preparation method according to claim 1, characterized in that: In the step (1), the solvent is a polar solvent, including one or more of dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, dimethylacetamide, cyclopentane, and acetonitrile.

4. The preparation method according to claim 1, characterized in that: In the step (2), the mass ratio of the inorganic salt to the organic sodium salt in the mixed solution C is (1-3): (1-5).

5. An amorphous metal oxide positive electrode material, characterized in that: The invention discloses a method for preparing the present invention according to any one of claims 1 to 4.

6. The amorphous metal oxide positive electrode material according to claim 5, characterized in that: The general formula of the amorphous metal oxide positive electrode material is Na x Ni y Mn 1-y O z , where 0.2≤x≤0.9, 0<y<1, 1≤z≤2.

7. A sodium ion battery positive electrode plate, characterized in that: The sodium ion battery positive electrode plate comprises an amorphous metal oxide positive electrode material as described in claim 5.

8. A sodium ion battery, characterized in that: The sodium ion battery comprises a sodium ion battery positive electrode plate as described in claim 7.

Citation Information

Patent Citations

  • Ultra-thin two-dimensional amorphous non-noble metal oxide material and preparation method and application thereof

    CN109817973A

  • Bivalent Metal Doping for Sodium Manganese Oxide as Cathode Materials for Sodium Ion Batteries

    US20180166686A1